COLLABORATIVE GOVERNANCE FOR SDGS' IMPLEMENTATION THROUGH KAMPUNG PROKLIM PROGRAM IN BODEYAN HAMLET SUKOHARJO - Septyanto Galan Prakoso; Ferdian Ahya Al Putra; Rino Ardian Nugroho; Siti Astiani Solihah (Center for Rural Areas Empowerment (P2D), Institut Teknologi Bandung, 2024)
Sustainable Development Goals (SDGs) are designed to tackle urgent global challenges. This study serves as an overview of the significance and interconnectedness of these three SDGs in fostering a sustainable future for our planet at a local level. Pro Iklim or Pro Climate is a program created by the Ministry of Environment and Forestry (KLKH) in 2011 which applies the concept of community empowerment or Community Based Development. The existence of Kampung Proklim (Program Kampung Iklim) program on the regency level in Indonesia can be a specific facet of the manifestation of SDGs, especially SDGs 13, 15, and 17. This article will discuss collaborative governance in managing climate action and the interlinkages between these SDGs and the Kampung Proklim program in Bodeyan Hamlet, Sukoharjo regency. Analysis will emphasize how the combined efforts can amplify the positive impact on global sustainability, even on the micro-local level. Qualitative descriptive methods will be used in this study, supported by on-site interview and library research. The study reveals that the 'Smart Proklim' program at Kampung Proklim Bodeyan implements an organic waste management program that is integrated with a smart garden. It is apparent that climate action and biodiversity preservation can be obtained through collaborative action among stakeholders. It also serves as an evidence where SDG 17 is the key to achieve SDG 13 to 15. This result shows the existence of collaborative governance, and at the same time answers three SDGs objectives. This remarks the uniqueness of this study.